(untitled) (Al-Qamar, 2023)
The concept of civilization is one of the oldest concepts of human society which evolved with human history. Civilization is a very important structural characteristic of an individual being a member of a society. Civilization improves the mental and moral powers of a person and encourages a person to lead a purposeful and civilized life. Culture also travels along with civilization. Culture has been defined as the highest manifestation of a material, civilized lifestyle, and concept of life. Language is the mirror of culture; Culture is the thing which is always moving for one era to other one with the passage of time while its roots remain same. There are also some differences in the meaning of civilization and culture which are found in different ways by different authors. According to whom culture is the name of the external aspect of our life while our inner thoughts and feelings reflect our culture. Civilization is a term based on thoughts and understanding because of which what comes into existence in practice is called culture.